Creating Spatial Information Infrastructures: Towards the Spatial Semantic Web - Oosterom, Peter van (CRC Press, 2009)
Initiatives, such as INSPIRE and the US DHS Geospatial Data Model, are working to develop a rich set of standards that will create harmonized models and themes for the spatial information infrastructure. However, this is only the first step. Semantically meaningful models must still be developed in order to stimulate interoperability.